2015
DOI: 10.1016/j.surfcoat.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polyethylene in an argon atmospheric pressure plasma jet

Abstract: The surface properties of polyethylene can successfully be altered using argon plasmas. In this work, the surface modification of low density polyethylene (LDPE) using an argon atmospheric pressure plasma jet (APPJ) is profoundly investigated. The surface modification is examined using different analysing techniques namely, water contact angle (WCA) measurements for the wettability and X-ray photoelectron spectroscopy (XPS) for the chemical composition. Particular attention is paid to the treatment distance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 28 publications
2
76
0
1
Order By: Relevance
“…Low-density polyethylene (LDPE) has become one of the most extensively used commodity polymers in various technological applications, such as adhesives, microelectronics, coatings, thin-films, catheters, medical implants, and orthopedic devices [1][2][3][4][5][6][7]. Its versatility is mainly attributed to its outstanding material properties, including low density, ease of finishing, durability, flexibility, and chemical resistance, as well as its current commercial availability.…”
Section: Introductionmentioning
confidence: 99%
“…Low-density polyethylene (LDPE) has become one of the most extensively used commodity polymers in various technological applications, such as adhesives, microelectronics, coatings, thin-films, catheters, medical implants, and orthopedic devices [1][2][3][4][5][6][7]. Its versatility is mainly attributed to its outstanding material properties, including low density, ease of finishing, durability, flexibility, and chemical resistance, as well as its current commercial availability.…”
Section: Introductionmentioning
confidence: 99%
“…Helium plasma-treated polycarbonate containing C, O, H atoms did not change the number of C and O atoms, but a change of structure by breaking carbonate groups was observed [53]. Helium is effective in increasing oxygen and also nitrogen functional groups coming from surrounding atmospheric air [47].…”
Section: Helium Bombardment/helium Plasmamentioning
confidence: 95%
“…In this case, plasma treatment causes wettability and hydrophilicity of surfaces by increasing the number of functional groups such as oxygen or nitrogen. Argon plasma treatment is able to increase oxygen functional groups on polymer surface if argon plasma discharge is working on atmospheric air [47]. Molecular dynamics (MD) simulation of bombardment of polymers showed that the main products of etching are CO or H 2 , polymer units and C x H y fragments during transient sputtering.…”
Section: Argon Bombardment/argon Plasmamentioning
confidence: 99%
“…In recent years, atmospheric pressure plasma jet (APPJ) that is low‐cost and easy‐to‐control has been studied and developed. Due to its preferable features including low‐cost and easy‐to‐control, there has been several research employing APPJ to hydrophilize PE . Deynse et al .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its preferable features including low‐cost and easy‐to‐control, there has been several research employing APPJ to hydrophilize PE . Deynse et al . modified the PE film by argon APPJ, and the results showed that the treated surface had better wettability.…”
Section: Introductionmentioning
confidence: 99%